2022
DOI: 10.3390/cells11162569
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids and PPAR Ligands: The Future in Treatment of Polycystic Ovary Syndrome Women with Obesity and Reduced Fertility

Abstract: Cannabinoids (CBs) are used to treat chronic pain, chemotherapy-induced nausea and vomiting, and multiple sclerosis spasticity. Recently, the medicinal use of CBs has attracted increasing interest as a new therapeutic in many diseases. Data indicate a correlation between CBs and PPARs via diverse mechanisms. Both the endocannabinoid system (ECS) and peroxisome proliferator-activated receptors (PPARs) may play a significant role in PCOS and PCOS related disorders, especially in disturbances of glucose-lipid met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 261 publications
0
7
0
Order By: Relevance
“…More precisely, PPARγ expression is activated upon folliculogenesis during the early follicle stages, leads to the large follicle stage, and is downregulated following the LH surge [118,119]. As far as the connection between PPARs and PCOS is concerned, Przybycie ń et al have recently reported on the role of PPAR ligands such as thiazolidinediones in PCOS, with a special focus on their link with the endocannabinoid system [40]. Nonetheless, no review of the literature has, to date, been published on the exclusive role of the PPAR isoforms in the pathophysiology of PCOS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More precisely, PPARγ expression is activated upon folliculogenesis during the early follicle stages, leads to the large follicle stage, and is downregulated following the LH surge [118,119]. As far as the connection between PPARs and PCOS is concerned, Przybycie ń et al have recently reported on the role of PPAR ligands such as thiazolidinediones in PCOS, with a special focus on their link with the endocannabinoid system [40]. Nonetheless, no review of the literature has, to date, been published on the exclusive role of the PPAR isoforms in the pathophysiology of PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the clinical features of PCOS may be classified as metabolic syndrome [11]. Moreover, a recent review focused on PCOS and infertility only [40]. In this regard, the purpose of the present literature review is to investigate the role of PPARs in the pathophysiology of PCOS, closely examine their implication in different molecular mechanisms associated with PCOS genesis and progression, as well as explore the feasibility of PPAR targeting for the treatment of PCOS.…”
Section: Introductionmentioning
confidence: 99%
“…52 The results of our study support earlier studies and propose that these mechanisms are involved in obesity and that the inflammatory mechanism inherent to PCOS may be mediated by GCs under the influence of DHEAS. Other pathways show that there are multiple pathways of PCOS that are activated when MGCs are exposed to DHEAS, such as alpha adrenergic receptor signaling, 53 beta adrenergic receptor signaling, 54 and endogenous cannabinoids, 55 along with the involvement of endothelin, GABA-B receptor II, interleukin, TGF-beta, thyrotropin-releasing hormone receptor, Toll receptor, VEGF, p38 MAPK, PGDF, and enkephalin release. Treatment of CGCs with DHEAS shows altered 2-arachidonoylglycerol biosynthesis, 56 adrenaline and noradrenaline biosynthesis, alpha adrenergic receptor signaling, 34 TGF-beta signaling, 57 Toll receptor signaling, 58 VEGF signaling, 59 and PI3 kinase.…”
Section: Discussionmentioning
confidence: 99%
“…PPARγ expressed in adipose tissues, liver, and skeletal muscles and PPARδ is expressed ubiquitously [ 176 ]. They recognize and bind diverse ligands, ranging from endogenous entities like fatty acids and eicosanoids to synthetic agents like fibrates and thiazolidinediones, and even diet-derived molecules like carotenoids and polyphenols [ 213 , 214 ]. They play an important role in several signaling pathways, including oxidative, inflammatory, AMPK, sirtuins, and mTOR.…”
Section: Nrs In Hmmentioning
confidence: 99%